SISTEM PENGELOLAAN ARSIP PADA UD. DEWI KOTA AMBON - Vera Paulin Kay; Vascolino Pattipeilohy (P3M Politeknik Negeri Ambon, 2023)
The archival system was developed with the aim of facilitating the storage and retrieval of information that is considered important to an organization. Archives have an important role in various agencies but this has not received attention at UD. Dewi where the files in the office are arranged irregularly and only arranged in several folders divided into folders of incoming mail and outgoing mail folders left piled on the table and placed in the file cabinet. This makes letters that are not archived properly easily scattered and lost. The purpose of this writing is that all archival management activities are good and in accordance with archival rules and provide input on good archival management procedures at UD. Goddess.The analytical method used in this study is Qualitative analysis, which is an analytical technique that describes problems based on theory, theory and severe expert opinions. The results of this study show that the archives at UD. The goddess has not complied with existing procedures, because the files in the office are arranged irregularly, and only arranged in several folders divided into incoming mail folders and outgoing mail folders and left piled on the table and placed in the filing cabinetConclusion of this writing Archive structuring system at UD. Dewi is not good because it is not in accordance with existing procedures and archive storage facilities are also inadequate because they only use one cabinet and folder to be stored and some are placed on the employee's desk. Employees who handle archives should attend archival training so that they better understand the arrangement of good archives.Keywords: Archive Setup